2021
DOI: 10.1186/s12871-021-01320-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of therapeutic caffeine in acute care postoperative and critical care settings: a scoping review

Abstract: Background Caffeine is the most utilised psychoactive drug worldwide. However, caffeine withdrawal and the therapeutic use of caffeine in intensive care and in the perioperative period have not been well summarised. Our objective was to conduct a scoping review of caffeine withdrawal and use in the intensive care unit (ICU) and postoperative patients. Methods PubMed, Embase, CINAHL Complete, Scopus and Web of Science were systematically searched fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…There are specific situations in which caffeine withdrawal occurs commonly, including the postoperative and ICU setting [26 ▪ ], fasting for Ramadan [27 ▪ ], and early pregnancy [28 ▪ ]. In the hospital setting, caffeine withdrawal syndrome (including headache) may adversely influence recovery from illness, prompting some to recommend caffeine supplementation for appropriate individuals [29]. A small randomized controlled study in migraine patients found that abrupt withdrawal from caffeine is a potent trigger for migraine [30], with severe attacks reported in seven of nine individuals who withdrew from caffeine and none when the same individuals continued caffeine.…”
Section: Caffeine Withdrawalmentioning
confidence: 99%
“…There are specific situations in which caffeine withdrawal occurs commonly, including the postoperative and ICU setting [26 ▪ ], fasting for Ramadan [27 ▪ ], and early pregnancy [28 ▪ ]. In the hospital setting, caffeine withdrawal syndrome (including headache) may adversely influence recovery from illness, prompting some to recommend caffeine supplementation for appropriate individuals [29]. A small randomized controlled study in migraine patients found that abrupt withdrawal from caffeine is a potent trigger for migraine [30], with severe attacks reported in seven of nine individuals who withdrew from caffeine and none when the same individuals continued caffeine.…”
Section: Caffeine Withdrawalmentioning
confidence: 99%
“…Of the seven prospective studies evaluating the effects of caffeine withdrawal, five studies showed that caffeine withdrawal increased the incidence of postoperative headache. Three studies have investigated the administration of caffeine for the relief of postoperative headache, including two prospective randomized controlled trials that concluded that the administration of caffeine prophylaxis reduces the incidence of postoperative headache [ 76 ].…”
Section: The Role Of Caffeine Withdrawal In Provoking Headachesmentioning
confidence: 99%